E-commerce Product Analysis Using Sentimental Analysis - P, Rathee (International Journal of Computer Sciences and Engineering, 2019)
Electronic commerce is a way of trading in different types of products, gadgets and services. It offers a wide variety of people’s comments and opinions. Sentimental analysis also known as opinion mining is a method of understanding people’s attitudes, sentiments, feelings expressed in those written comments. This is an e-commerce web application tackles with sentence level sentimental analysis which fetches and classify the polarity of reviews as positive, negative and neutral. All those reviews are ranked based on this polarity that helps the user to make a smart choice among good, bad and worst products. This aims to reduce the time and effort of the user in searching for specific product on e-commerce website.